Timing of ovarian stimulation in patients prior to gonadotoxic therapy: an analysis of 684 stimulations. (April 2016) - von Wolff, Michael; Capp, Edison; Jauckus, Julia; Strowitzki, Thomas; Germeyer, Ariane; ,
Abstract: Objective: Time to therapy initiation in patients requiring gonadotoxic therapy is crucial. This article evaluates the efficiency of random start ovarian stimulation in affected women. Study design: Retrospective anonymous registry data analysis from 85 university and non-university fertility centres participating in the international network FertiPROTEKT. The study comprised 684 women undergoing ovarian stimulation for fertility preservation from 2007 to 2013. According to the time of stimulation initiation, days of ovarian stimulation, total dose of gonadotropins used, gonadotropin dose used per day, number of oocytes retrieved and incidence of ovarian hyperstimulation syndrome were analysed. Statistical analysis was performed using analysis of variance in case of continuous outcome variables and chi-square tests in case of categorical variables. Results: Among 684 women who underwent ovarian stimulation prior to gonadotoxic therapy 472 (69.0%) started ovarian stimulation between menstrual cycle day 1–5 (group A), 109 (15.9%) between day 6–14 (group B) and 103 (15.1%) after day 14 (group C). The days of stimulation (A: 10.8 ± 2.4, B: 10.6 ± 2.7, C: 11.5 ± 2.2) and total dose of gonadotropins (A: 2496 IU ± 980, B: 2529 IU ± 940, C: 2970 IU ± 1145) were significantly increased in group C. Numbers of obtained oocytes (Group A: 11.6 ± 7.7, B: 13.9 ± 9.1, C: 13.6 ± 7.9) were significantly increased in group B and C, while the overall incidence of ovarian hyperstimulation syndrome III° was 0.15%. Conclusion: The outcome of ovarian stimulation is similar after stimulation initiation during any phase of the menstrual cycles, supporting the concept of random-start ovarian stimulation before gonadotoxic therapy without disadvantage for the patient concerning later fertility preservation.